Disability Inclusion in Graduate Competencies in Medical Education: What Competencies Matter? - Whitehead, Sarah; Amosun, Seyi Ladele; Lorenzo, Theresa; Kathard, Harsha (International Journal of African Higher Education, 2025)
In South Africa, negative attitudes of medical doctors towards persons with disabilities is evident. A doctoral study was carried out to explore medical doctors’ current practices with persons with disabilities to determine their competencies in providing quality inclusive health care, guided through the lens of attitudes to ensure a very close link with knowledge and skills. The participants included persons with disabilities, medical doctors, medical students, and allied health professionals. Using the ICF framework and a mixed-method design that included focus group discussion, in-depth interviews, and a modifed Delphi technique, thirteen disability-inclusive competencies and nine sub-competencies were generated. The article describes the process by which the competencies were generated, with three global initiatives providing the background. The proposed competencies can address the issues across the four diﬀerent mechanisms that could negatively impact the quality of healthcare that persons with disabilities receive.